2019
DOI: 10.1097/ana.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Electroencephalography and Automated Pupillometry in Critically Ill Patients: A Pilot Study

Abstract: Background: Electroencephalography (EEG) is widely used in the monitoring of critically ill comatose patients, but its interpretation is not straightforward. The aim of this study was to evaluate whether there is a correlation between EEG background pattern/reactivity to stimuli and automated pupillometry in critically ill patients. Methods: Prospective assessment of pupillary changes to light stimulation was obtained using an automated pupillometry (NeuroLight Algiscan, ID-MED, Marseille, France) in 60 adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Autonomic dysfunction mediated by in ammatory response likely has an important role in the pathogenesis of the dysfunction of the brain or other organs [36]. Neurotransmitter imbalance such as cholinergic de ciency due to in ammation and multiorgan dysfunction in critically ill patients can lead to pupillary dysfunction [18,33]. In this context, although there is limited evidence on the association between QP values and the severity of encephalopathy [37], QP as an indicator of autonomic and brain dysfunction may play a role in assessing the severity of metabolic encephalopathy as the cause of HOU (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic dysfunction mediated by in ammatory response likely has an important role in the pathogenesis of the dysfunction of the brain or other organs [36]. Neurotransmitter imbalance such as cholinergic de ciency due to in ammation and multiorgan dysfunction in critically ill patients can lead to pupillary dysfunction [18,33]. In this context, although there is limited evidence on the association between QP values and the severity of encephalopathy [37], QP as an indicator of autonomic and brain dysfunction may play a role in assessing the severity of metabolic encephalopathy as the cause of HOU (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, QP was shown to be useful in neurological prognostication in unconscious patients after cardiac arrest [11][12][13][14][15][16][17]. Because the PLR is regulated by the autonomic nervous system, QP may also have a role in the assessment of autonomic dysfunction in critically ill patients [18,19]. However, studies on the QP ndings in patients who are hospitalized outside intensive care units are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Automated pupillometry is a bedside technique able to precisely quantify the pupillary size and pupillary light reflex (PLR). Change in pupillary activity showed a good accuracy to predict delirium in ventilated critically ill patients and to detect unreactive EEG background ( Favre et al, 2020 , Hasan et al, 2019 ). As such, automated pupillometry could be also used to titrate the administration of anaesthetics or analgesics, as excessive drug regimens would provide reduced PLR or size, respectively, or identify patients at risk of delirium (i.e.…”
Section: How Nurses Can Adequately Use Neuromonitoring At the Bedsidementioning
confidence: 99%
“…A pilot study showed that the reduction in pupillary constriction rate to light stimulation derived from automated pupillometry identified patients “at risk” of an unreactive background EEG ( 12 ). However, this study had several limitations, including the small sample size, lack of adjustment for several confounders, e.g., use of sedatives or underlying brain injury, and lack of additional automated pupillometry-derived variables, such as the Neurological Pupil index (NPi), which has been shown to predict neurological outcome in critically ill patients ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%